Knowledge and governance arrangements in agricultural production: Negotiating access to arable land in Zarafshan Valley, Tajikistan - Andreas Mandler (University of Bonn, Center for Development Research (ZEF), 2012)
The economy and society of Tajikistan depends strongly on agriculture. Approximately three-quarters of the Tajik population live in rural areas. The agricultural sector generates about one fifth of total GDP and provides 55 per cent of employment (Akramov and Shreedhar, 2012). However, this does not translate into a sufficient agricultural output. On the one hand, the natural conditions of the country are not particularly favourable for agriculture, as its high elevation limits the land area that is suitable for farming. On the other hand, national legislation and local governance arrangements are not always conducive to agricultural production. The present paper inquires into the role of knowledge and governance in local agricultural production. It concentrates on access to arable land in the upper Zarafshan Valley, a remote mountainous area in northern Tajikistan. The paper analyses how the individual knowledge of farmers relates to the common knowledge that is represented by local governance arrangements. To exemplify this relation it focuses upon one local institution that implements land distribution, Bobogi. The shifting status of knowledge and institutions enables farmers to exercise influence on negotiation processes of access to land. Bobogi is seen to be a publicly legitimized institution that contributes to the construction and maintenance of social order in local communities.
Keywords: 330; Agriculture; governance; knowledge; social order; Bobogi; Zarafshan Valley; Tajikistan